Perancangan Sistem Pengukuran Kinerja Pada Perguruan Tinggi Swasta XYZ Dengan Metode Balanced Scorecard - Wahyudi Sutopo; Eko Liquiddanu; Endah Sulistyowati (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2005)
To face globalization era that led to a more competitive, a higher education institution need to set up a strategic management system in order to develop its organization performance to survive and winning the competition. To set up strategic management, the institution must exactly recognize the performance level of it’s organization. That’s why the performance measurement system to help the organization enhance its performance is needed.XYZ college as a higher institution, wants to improve it’s performance by developing a management system to evaluate the current implemented strategy. The balanced scorecard approach as one of performance measurement method by integrating financial and non financial measures is used to design the the performance measurement system in this research. The balanced scorecard design of XYZ college constructed by considering the model from BAN, Competitive Funding Scheme, and the result from other researches. To accommodate the vision, mision, and objective of the XYZ institusion, this research involved thirthteen respondent who are executives management that consist of: Director; director assistant, and department chairmans. After the performance measurement system designed using balanced scorecard method, the weight of each perspectives, objective criterias, and performance indicators then calculated using AHP method. Next, performance level of institusion represented by 1-10 scale based on OMAX. This research present the XYZ College performance measurement result of 2004 and proposes strategic suggestion to enhance the institution performance.